Direct Observation of a Cyclic Vinyl Polymer Prepared by Anionic Polymerization using N‐Heterocyclic Carbene and Subsequent Ring‐Closure without Highly Diluted Conditions. Issue 10 (8th April 2020) - Naruse, Keiji; Takasu, Akinori; Higuchi, Masahiro
Abstract: A 1:1 adduct of methyl sorbate (MS) and 1, 3‐di‐ tert ‐butylimidazol‐2‐ylidene (NHC t Bu) initiates anionic polymerization of a nonconjugated polar alkene, allyl methacrylate (AMA) in toluene at −20 °C. After the monomer is consumed quantitatively using a bulky aluminum Lewis acid, methylaluminum bis(2, 6‐di‐ tert ‐butyl‐4‐methylphenoxide) (MAD), as an additive, successive ring‐closure occurs without highly dilute conditions to give a cyclic poly(AMA) containing α‐terminal MS unit, and an M n of 8.8 × 10 3 −58.5 × 10 3 with a narrow molecular dispersity index ( M w / M n = 1.14 –1.37 ). The lack of a need for dilution is due to the fact that an α‐terminal NHC t Bu group is acting as the counter cation for the propagating center in the polymerization. From 1 H NMR and matrix assisted laser desorption/ionization (MALDI‐TOF) mass spectra, combined with transmittance electron microscope (TEM) observation of a synthesized poly(AMA) with longer alkyl side chains prepared via a thiol‐ene click reaction, it is concluded that once the monomer is consumed, nucleophilic attack at the neighboring methine of the α‐terminal NHC t Bu residue by the propagating anionic center causes ring‐closing to cyclic poly(AMA). Abstract : A 1:1 adduct of methyl sorbate and 1, 3‐di‐ tert ‐butylimidazol‐2‐ylidene initiated anionic polymerization of allyl methacrylate (AMA) in the presence of a bulky aluminum Lewis acid is reported. From transmittance electron microscope direct observation, it is concluded that once the monomer has been consumed, nucleophilic attack at α‐terminal NHC t Bu residue by the propagating anionic center causes ring‐closing to cyclic poly(AMA) without highly diluted conditions.